The novel p.Cys65Tyr mutation in NR5A1gene in three 46,XY siblings with normal testosterone levels and their mother with primary ovarian insufficiency - Helena Fabbri‐Scallet; Juliana Gabriel Ribeiro de Andrade; Fernanda Caroline Soardi; Flávia Leme de Calais; Reginaldo José Petroli; Andréa Trevas Maciel‐Guerra; Gil Guerra‐Júnior; Maricilda Palandi de Mello (2014)
Abstract Background Disorders of sex development (DSD) is the term used for congenital conditions in which development of chromosomal, gonadal, or phenotypic sex is atypical. Nuclear receptor subfamily 5, group A, member 1 gene ( NR5A1 ) encodes steroidogenic factor 1 (SF1), a transcription factor that is involved in gonadal development and regulates adrenal steroidogenesis. Mutations in the NR5A1 gene may lead to different 46,XX or 46,XY DSD phenotypes with or without adrenal failure. We report a Brazilian family with a novel NR5A1 mutation causing ambiguous genitalia in 46,XY affected individuals without Müllerian derivatives and apparently normal Leydig function after birth and at puberty, respectively. Their mother, who is also heterozygous for the mutation, presents evidence of primary ovarian insufficiency. Case presentation Three siblings with 46,XY DSD, ambiguous genitalia and normal testosterone production were included in the study. Molecular analyses for AR , SRD5A2 genes did not reveal any mutation. However, NR5A2 sequence analysis indicated that all three siblings were heterozygous for the p.Cys65Tyr mutation which was inherited from their mother. In silico analysis was carried out to elucidate the role of the amino acid change on the protein function. After the mutation was identified, all sibs and the mother had been reevaluated. Basal hormone concentrations were normal except that ACTH levels were slightly elevated. After 1 mcg ACTH stimulation test, only the older sib showed subnormal cortisol response. Conclusion The p.Cys65Tyr mutation located within the second zinc finger of DNA binding domain was considered deleterious upon analysis with predictive algorithms. The identification of heterozygous individuals with this novel mutation may bring additional knowledge on structural modifications that may influence NR5A1 DNA-binding ability, and may also contribute to genotype-phenotype correlations in DSD. The slightly elevated ACTH basal levels in all three patients with 46,XY DSD and the subnormal cortisol response after 1 mcg ACTH stimulation in the older sib indicate that a long-term follow-up for adrenal function is important for these patients. Our data reinforce that NR5A1 analysis must also be performed in 46,XY DSD patients with normal testosterone levels without AR mutations.